Protective vacuum-arc coatings on zirconium alloy fuel cladding to prevent catastrophic accidents at nuclear reactors - Kuprin, A.S.; Zuyok, V.A.; Belous, V.A.; Ovcharenko, V.D.; Reshetnyak, E.N.; Vasilenko, R.L.; Tolmachova, G.N.; Kushtym, Ya.O. (Problems of Atomic Science and Technology, 2023)
The processes of vacuum arc deposition of multicomponent coatings based on Cr, Ti, Al, Fe, Y, Si, and their nitrides with a thickness of 5…9 μm for the protection of zirconium alloy fuel rods were developed. The composition, structure, and mechanical properties of the coatings were determined by electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffraction analysis, and nanoindentation. Comparative studies of the protective properties of coatings during high-temperature oxidation of Zr1Nb tubes were carried out. It was found that metal coatings with a high chromium content have excellent protective properties during tests under simulated accident conditions. They are simultaneously resistant to high-temperature corrosion in air at 750…1100 °C and in water steam during thermal cycling up to 1020 °C. Hard nitride coatings, which significantly strengthen the surface of the zirconium alloy and provide good protection against oxidation in air, are less effective in water steam under thermal cycling. The coatings and processes of synthesis developed at NSC KIPT can be useful for improving fuel cladding made of zirconium alloys of the world’s leading nuclear fuel producer Westinghouse Electric Company. Розроблено процеси вакуумно-дугового осадження багатокомпонентних покриттів на основі Cr, Ti, Al, Fe, Y, Si та їх нітридів товщиною 5…9 мкм для захисту оболонок твелів з цирконієвих сплавів. Склад, структуру та механічні властивості покриттів визначено методами електронної мікроскопії, енергодисперсійної рентгенівської спектроскопії, рентгеноструктурного аналізу та наноіндентування. Проведено порівняльні дослідження захисних властивостей покриттів при високотемпературному окисленні труб Zr1Nb. Було виявлено, що металеві покриття з високим вмістом хрому мають високі захисні властивості під час випробувань в імітованих умовах аварії. Вони одночасно стійкі до високотемпературної корозії на повітрі при температурі 750…1100 °С і у водяній парі при термоциклуванні до 1020 °С. Тверді нітридні покриття, які значно зміцнюють поверхню цирконієвого сплаву і добре захищають від окислення на повітрі, менш ефективні в парах води при термоциклуванні. Розроблені у ННЦ ХФТІ покриття та процеси синтезу можуть бути корисні при вдосконалені топливних оболонок із сплавів цирконію провідного світового виробника ядерного палива Westinghouse Electric Company.